Development of PJOK Learning E-Module Based on Play Activities on Physical Freshness Materials for Grade 2 Junior High School - Afif, Muhammad Fajar; Komari, Amat (STKIP Singkawang, 2024)
This research aims to develop a game-based physical education and sports e-module on physical fitness materials for 8th grade students. The data in this study were analyzed using Miles & Huberman's qualitative data analysis technique which includes data reduction, data presentation, and conclusion drawing. In the analysis stage, a needs analysis, curriculum analysis, and student characteristics analysis were carried out through observations, interviews, and literature studies. Based on the analysis results, the e-module was designed by integrating physical fitness materials and game activities suitable for junior high school students' characteristics. The e-module development involved creating interactive multimedia, educational games, and formative evaluations. The e-module implementation was conducted in 8th grade classes, followed by a summative evaluation to test the product's effectiveness. The research results show that this game-based physical education e-module is effective in improving students' understanding of physical fitness concepts and active participation in physical activities. This product can be used as an innovative and engaging alternative learning resource for students in learning physical fitness materials